The mediating effect of knowledge of the investment protection act on investment decision-making in an emerging country - Long Tran Viet; Hai Phan Thanh (Cogent Social Sciences)
This study aims to determine the factors and their influence on the investment decisions of individual investors in the Vietnamese market. Using SPSS and AMOS 25 softwares, the study used CRA, EFA, SEM, and Bootstrap analysis techniques to test the hypotheses of the linear structure model. A total of 263 individual investors currently investing in the retail sector in several enterprises in several major cities in Vietnam agreed to participate in the research. The findings show that knowledge of the investment protection acts positively impacts investors’ decision-making in which the factors of information about enterprises or investment projects, supporting policies and calling for investment, and investors’ experiences have both direct positive and indirect positive effects through the investors’ knowledge and understanding of the law for making investment decisions. Meanwhile, this understanding of investors is positively and directly affected by five factors of information about the business or investment project, supporting policies and calling for investment, investors’ experience, investment advice, and provisions of the law on investment protection. The study’s results also provide empirical evidence that word-of-mouth information does not affect investors’ knowledge of investment protection laws and decision-making. Meanwhile, the provisions of the current investment protection law in Vietnam have an indirect impact on decision-making. The study results are the basis for improving the legal system on investment protection in Vietnam and governance implications for investors when doing investment research in this market.